Pencabutan Putusan Pailit Dalam Hal Harta Pailit Tidak Cukup Untuk Membayar Biaya Kepailitan - Paulus Sirait; Muhammad Junaidi; Kukuh Sudarmanto; Syafran Sofyan (Jurnal USM Law Review)
The purpose of this research is to learn about the revocation of bankruptcy judgments in the event that bankruptcy assets are not sufficient to pay bankruptcy costs. If, in the management of bankruptcy assets, the curator considers that the bankruptcy assets are insufficient to pay the bankruptcy costs, the curator may apply for revocation of the bankruptcy statement submitted to the supervisory judge. Based on the proposal of the supervisory judge to revoke the debtor's bankruptcy statement, the commercial court may decide to revoke the debtor's bankruptcy statement. The problems that occur over the revocation and the problems and solutions to the revocation of the bankruptcy judgment in the event that the bankruptcy assets are not enough to pay the bankruptcy costs. The research method used is a legal research method that prioritizes how to research library materials and laws and regulations. The results of this study indicate that the revocation of the bankruptcy decision prioritizes legal certainty for debtors but does not provide certainty of payment of creditors' bills. Second, the revocation of the bankruptcy declaration decision by the Commercial Court has caused problems where the bankruptcy assets are only used to pay bankruptcy costs; the bankruptcy revocation decision is not accompanied by an order for the receivership to liquidate the company's debtors; and actio pauliana in bankruptcy is only valid while the bankruptcy process is still running.